COMPARISON OF LEUKOCYTE PROFILE IN CAT FEEDED TRADITIONAL AND COMMERCIAL FOOD WITH AND WITHOUT THE ADDITION OF BLACK SOLDIER FLY MAGGOT OIL - Caroline, Grace; Gunawan, I Wayan Nico Fajar; Dharmayudha, Anak Agung Gde Oka (Buletin Veteriner Udayana, 2023)
The increasing population of cats, makes the need for cat food also increases. BSF maggot cultivation is a trend in Indonesia, as for the products produced such as BSF maggot oil. BSF maggot oil can be used as an additional supplement because of its high protein content. Several studies have shown that the Black Soldier Fly maggot is an insect that is high in protein which is considered to be able to meet the protein needs in the body. This study aims to compare the leukocyte profile in cats fed traditional diets and cats fed commercial feeds with BSF maggot oil added to both feeds, and to determine whether BSF maggot oil affects leukocytes in cats that consume them. The study used 24 samples of cat blood aged approximately one to three years. Furthermore, they were divided into four treatment groups. The control group is a cat that is fed commercial food (P0), the first treatment group is a cat that is fed commercial food with the addition of BSF maggot oil (P1), the second treatment group is a cat that is given traditional food in the form of boiled tuna (P2), and lastly, the third treatment group was cats that were fed traditional food with BSF maggot oil (P3) added. The data from the examination were analyzed using the variance test (ANOVA), to see the effect between treatments, followed by Duncan's test. The results of this study indicate that the treatment of dry commercial feed and traditional feed added with black soldier fly magot oil statistically there was a significant difference in the values ??of neutrophils, eosinophils, and lymphocytes in the cat group (P0) with (P1) (P<0.05), but not there was a significant difference between groups (P2) and (P3) (P>0.05).